Research progress of knee fibrosis after anterior cruciate ligament reconstruction - Liang, YangYang; Zhang, QingQing; Fan, YouFei (Frontiers in Pharmacology, 2024)
Anterior cruciate ligament (ACL) injury is a common sports injury, and ACL reconstruction is an effective surgery for this trauma. Most cases gain good recovery after surgery, while some may experience knee stiffness, which is characterized by joint fibrosis, leading to reduced joint mobility, pain, and dysfunction. Currently, various researches have been conducted in unveiling the mechanisms of this condition, identifying pre-, intra-, and post-operative risk factors, as well as testifying the efficacy of different therapeutic methods against this condition. In this review, we summarized the current progress regarding the advancements in knee fibrosis after ACL reconstruction. The risk factors associated with knee fibrosis are systematically delineated, accompanied by an evaluation of the efficacy of various treatment modalities in both the prevention and mitigation of fibrosis. Furthermore, recommendations for future research directions are proposed, offering a foundational basis for subsequent investigations.